Sero-epizootological evaluation of Brucellosis in Bovines - RAJU, S; KOLHE, R P; RAUT, C; SHINDE, S V; ZADE, N N; ZADE, N N (The Indian Journal of Animal Reproduction, 2007)
A total of245 serum samples from 125 cattle and 120 buffalos were collected and screened for brucellosis. Screening by serological tests viz., RBPT, STAT, EDTA- STAT, MET and dot-ELISA was done. The overall sero prevalence was recorded 19.00, 20.83; 20.00, 18.33; 14.40, 11.66; 17.60, 15.00 and 6.00, 0.00 per cent by RBPT, STAT, EDTA-STAT, MET and dot-ELISA in cattle and buffaloes respectively. Prevalence rate was found to vary with the test used. The predictive values obtained revealed no difference between the values of test and true prevalence in cattle, but little variation in buffaloes was recorded in terms oftest employed. The findings of present investigation led to conclusion; that serological tests should be used in combination. The studies on point prevalence, test and true prevalence, mean titre values and predictive values of the serological tests shall be considered as markers in sero-epizootological evaluation of brucellosis in population.